Evaluasi Akuntabilitas Kinerja Pemerintah Provinsi Daerah Khusus Ibukota Jakarta - Budi Mulyana (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2021)
One of the important areas of change in bureaucratic reform agenda in Indonesia is performance accountability which is intended to promote a government management system that focuses on results-oriented performance improvement. The purpose of this research is to evaluate the factors causing Government of the Special Capital Region of Jakarta Province had not reached the targeted predicate until the 2019 Fiscal Year and formulate recommendations to improve it's predicate in Performance Accountability. The research method used is a qualitative method, a case study approach. Data analysis was carried out based on documentation study, observation and focus group discussion (FGD). The research was conducted from September to December 2020.